Gentle Sterilization of Carrot-Based Purees by High-Pressure Thermal Sterilization and Ohmic Heating and Influence on Food Processing Contaminants and Quality Attributes - Gratz, Maximilian; Sevenich, Robert; Hoppe, Thomas; Schottroff, Felix; Vlaskovic, Nevena; Belkova, Beverly; Chytilova, Lucie; Filatova, Maria; Stupak, Michal; Hajslova, Jana; Rauh, Cornelia; Jaeger, Henry (Frontiers in Nutrition, 2021)
High-pressure thermal sterilization (HPTS) and Ohmic heating (OH) are two emerging sterilization techniques which to this point still lack implementation in the food industry. However, both technologies offer significant benefits in terms of spore inactivation in food products with reduced thermal intensity as well as minimized effects on sensory and nutritional profiles. In this study, HPTS and OH were tested based on possible food safety process windows in comparison to thermal retorting to optimize the food quality of a chicken rice puree (suitable for baby food). Tested parameters related to food quality were texture, carotenoid content, color and amount of food processing contaminants (FPC) formed. Application of the innovative sterilization techniques resulted in a better retention of color, texture, and carotenoids (for HPTS) as well as a reduced formation of food processing contaminants. Particularly, a significant reduction of furan and its derivates formation could be observed compared to the retorted samples. Hence, both sterilization technologies showed promising results for a mitigation of potential toxic processing contaminants and retention of quality attributes.